Climate Communication and Indian Media: Challenges and Responses - Dwivedy, Ashish Kumar; Kara, Priyadarshi; Sriranjan, Priti; Nayak, Bholanath; Jena, Bikram Keshori (Issues in Social Science, 2024)
Fast-depleting natural resources, global warming, and the consequent anthropogenic climatic change pose a severe threat to the very existence of life on our planet. Being a public concern, the problem for its solution, requires active public participation. It plays a crucial role by mobilising people against the rampant exploitation of nature. Past researchers have analysed the role of media in this direction. This paper takes a stride in this direction by engaging with Gateway Belief Model and scrutinising how communicating scientific consensus through media impacts the belief in climate change and produces support for action. It also discusses the challenges media face in its attempts to communicate nature to the public. By focussing on examples from the Indian media, this paper problematises the intersection between religious belief and scientific research to underpin the relationship between public perception and policy prescription regarding the climate change crisis.